Cambiando de perspectiva: cautivos en el interior de la frontera - Aguirre, Susana (Centro de Historia Argentina y Americana, 2007)
This work focuses on the captive Indians, ignored characters in the official history, that were silenced victims too, fruit of the ambivalent relationship -pacific and violent- between the indigenous and Spanish world. The emphasis is put in the official policy since its captivity, giving special attention to the distribution, the modality of deposits, distinguishing those emanated from other causes.